IMPLEMENTASI KURIKULUM ANAK BERKEBUTUHAN KHUSUS DI LENTERA HATI SCHOOL KUDUS - Rahmawati, Ruchaini Fitri (QUALITY, 2019)
There are so many problems about curriculum, including the curriculum for children with special needs. For example, curriculum in inclusive schools cannot be applied properly due to the lack of human resources mastery on the curriculum itself. This study aims to find out how the implementation of curriculum for children with special needs in Lentera Hati School and what are the supporting factors and obstacles in implementing the curriculum. This research was field research that used a descriptive analytic qualitative approach.The results of this study are: the implementation of the curriculum at Lentera Hati School includes curriculum planning described in RPPM and RPPH which refers to the 2013 PAUD curriculum which is then modified by decreasing the learning achievement standards according to the students’ needs and abilities. Child classification is based on the student’s mental age and ability. RPPH is designed as flexible as possible because classes are heterogeneous. The core activities of learning refer to the development of Religious and Moral Values, Motoric Physical, Cognitive, Language, Social Emotions, Art and Creativity. Learning media are used to prioritize the effective and efficient and safe principles for students. The scoring system is based on assessment from the teacher and the results of therapy.Keywords: Curriculum, Children with Special Needs, Early Childhood Education.